Tumor classification for early oral cancer: Re‐evaluate the current TNM classification. Issue 2 (21st March 2014) - (Hubert) Low, Tsu‐Hui; Gao, Kan; Elliott, Michael; Clark, Jonathan R
ABSTRACT Background We hypothesized that incorporation of tumor thickness into the tumor–node–metastasis (TNM) system will provide better prognostic information. Tumors were reclassified as T1 if ≤5‐mm thick/≤4‐cm diameter, and T2 if >5‐mm thick/≤4‐cm diameter. Methods A retrospective analysis was conducted of 322 patients with T1 and T2 oral squamous cell carcinoma (SCC) between 1987 and 2012. Univariable survival analysis was performed using the log‐rank test and multivariable analysis using the Cox proportional hazards model. Results Multivariable analysis confirmed that tumor thickness is the most important predictor of disease‐specific survival (DSS; hazard ratio [HR], 2.7; p = .03) and overall survival (OS; HR, 2.9; p = .001). Using the current TNM classification system, there is no significant difference in survival between the T1 and T2 groups for DSS (p = .13) or OS (p = .66). The revised staging system was superior at stratifying patients according to the T classification for both DSS (p = .016) and OS (p < .001). Conclusion Tumor thickness is an important prognostic indicator in early oral SCC and should be incorporated in the TNM classification system. © 2014 Wiley Periodicals, Inc. Head Neck37: 223‐228, 2015